FISH Handbook for Biological Wastewater Treatment - Nielsen, Per; Daims, Holger (IWA Publishing, 2009)
The FISH Handbook for Biological Wastewater Treatment provides all the required information for the user to be able to identify and quantify important microorganisms in activated sludge and biofilms by using fluorescence in situ hybridization (FISH) and epifluorescence microscopy. It has for some years been clear that most microorganisms in biological wastewater systems cannot be reliably identified and quantified by conventional microscopy or by traditional culture-dependent methods such as plate counts. Therefore, molecular biological methods are vital and must be introduced instead of, or in addition to, conventional methods. At present, FISH is the most widely used and best tested of these methods. This handbook presents all relevant information from the literature and, based on the extensive experience of the authors, advice and recommendations are given for reliable FISH identification and quantification.